2015-2023: Ocho años de política lingüística en Aragón Balance relativo al aragonés - José Ignacio López Susín (Lengas)
After the regional elections of May 2015, the PSOE-CHA pact led to the creation, for the first time in Aragon, of a general directorate for language policy that would develop the provisions of Article 7 of the Statute of Autonomy (EAA) and give content to what appears as one of the first exclusive competences of the Autonomous Community, the fourth in the rank established in Article 71 of the EAA, only behind the organisation of the institutions of self-government and substantive and adjective foral law. The directorate general was abolished by the new PP-VOX government, with the support of the PAR, after the 2023 elections.This article takes stock of these two legislatures in which, without modifying the regulatory law, the names of the languages (Aragonese and Catalan of Aragon), which had been replaced in the previous period by ahistorical and unscientific geographical names (with the acronyms LAPAO and LAPAPYP), have been recovered, and their development in the fields of social promotion and teaching has been carried out.